2016
DOI: 10.1007/s13337-016-0330-z
|View full text |Cite
|
Sign up to set email alerts
|

First report of detection and molecular characterization of porcine parvovirus in domestic and wild pigs in Kerala, India

Abstract: Porcine parvovirus (PPV) is a DNA virus of the genus Parvovirus of family Parvoviridae. It is the causative agent of many disease problems in pigs such as maternal reproductive failure, stillbirth, mummification, embryonic or fetal death, infertility, abortion and neonatal death. A study was conducted to assess the incidence of the virus in pigs in Kerala State in South India. A total of 38 samples were collected from domestic and wild pigs from different districts of the State. Polymerase chain reaction targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Twenty fetal tissue samples were tested for PPV by PCR targeting NS1 gene of the virus (Fig 5). Of the samples tested, 19 were found positive by PCR with a percentage positivity of 95% unlike Aishwarya et al (2016) who reported 5.26% (2/38) positivity for PPV in tissues samples. Serena et al (2019) reported 7/131 samples from tissues of still birth and mummified fetuses were positive to PPV by PCR in Argentina.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…Twenty fetal tissue samples were tested for PPV by PCR targeting NS1 gene of the virus (Fig 5). Of the samples tested, 19 were found positive by PCR with a percentage positivity of 95% unlike Aishwarya et al (2016) who reported 5.26% (2/38) positivity for PPV in tissues samples. Serena et al (2019) reported 7/131 samples from tissues of still birth and mummified fetuses were positive to PPV by PCR in Argentina.…”
Section: Resultsmentioning
confidence: 81%
“…The positive isolates were related to the PPV 1 sequence (NADL-2), maintaining the amino acid differences in positions 436 (S-P) and 565 (R-K) (Serena et al, 2019). The prevalence of PPV genotypes 1-7 have been reported worldwide (Streck et al, 2013;Xioa et al, 2013;Schirtzinger et al, 2015 andXing et al, 2018) in India (Sharma and Saikumar, 2015;Aishwarya et al, 2016). PPV 1 is known as one of the most important causes of reproductive failure in swine (Streck et al, 2013).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations